Risk Factors for Stunting among Children in Indonesia: A Systematic Review - Hamidah Retno Wardani (KHD Production, 2024)
The incidence of short toddlers or commonly referred to as stunting is one of the nutritional problems experienced by toddlers in the world today, including Indonesia. Indonesia is a developing country with a stunting prevalence in 2022 of 21.6 percent. This figure is lower than the 2021 figure of 24.4 percent. The incidence of stunting in developing countries can be influenced by various risk factors. This study aims to analyze the risk factors for stunting in toddlers aged 12-59 months. The study was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The results obtained from the analysis of 8 journals show that there are several risk factors that have an important role in the prevalence of stunting in toddlers. Among them are breastfeeding history, maternal nutritional status, parental education, parental height, parental education, ANC visits, parental income, energy adequacy, fat and protein intake and the level of knowledge of mothers, especially about nutrition. However, there are several risk factors that do not have a significant relationship with the incidence of stunting in toddlers including dietary restrictions, consumption of Fe tablets in mothers, history of comorbidities, clean water sanitation, smoking environment, and economic conditions. Stunting is not only related to children's height below the standard.